COMPARATIVE EVALUATION OF SEQUENTIAL INTRAOPERATIVE USE OF WHOLE BLOOD FOLLOWED BY BRILLIANT BLUE VERSUS CONVENTIONAL BRILLIANT BLUE STAINING OF INTERNAL LIMITING MEMBRANE IN MACULAR HOLE SURGERY. Issue 8 (August 2016) - Ghosh, Basudeb; Arora, Supriya; Goel, Neha; Seth, Anisha; Pyare, Richa; Sridharan, Preethi; Thakar, Meenakshi
Abstract : Purpose: To compare the structural and functional outcome of use of autologous heparinized whole blood before staining internal limiting membrane with brilliant blue (BB) versus conventional BB–assisted macular hole surgery. Methods: Sixty eyes of 60 patients were randomly divided equally in Group A (BB staining using whole blood) and Group B (conventional BB staining). Clinical assessment and spectral domain optical coherence tomography was done at baseline and 3 weeks, 6 weeks, 16 weeks, and 6 months postoperatively. Results: Group A eyes had a significantly higher best-corrected visual acuity as compared with Group B postoperatively ( P < 0.001, <0.001, 0.004, 0.04 at 3, 6, 16 weeks, and 6 months). Inner segment/outer segment junction continuity was noted in greater number of eyes in Group A compared with Group B ( P = 0.02, 0.002, 0.003, and 0.03 at 3, 6, 16 weeks, and 6 months). Eyes in Group A had significantly higher outer foveal thickness at 3 weeks ( P = 0.001) and 6 weeks ( P < 0.001) compared with Group B. Conclusion: Use of whole blood before staining internal limiting membrane with BB causes earlier and better visual rehabilitation postoperatively, which could be attributed to earlier photoreceptor regeneration as evidenced by inner segment/outer segment junction continuity and increase in outer foveal thickness. Abstract : Sequential intraoperative use of autologous heparinized whole blood before staining internal limiting membrane with brilliant blue dye protects against dye toxicity and prevents inadvertent subretinal migration of dye. It improves functional outcome of macular hole surgery by earlier restoration of photoreceptor outer segments.